تأثير تداخل المحتويات على المهارات التي تخضع لبرنامج حركي عام ( التصويب في كرة السلة ) - فاضل, رغد; معوض, وائل; الصوفي, محمد (Latakia University Journal -Medical Sciences Series, 2016)
مع ظهور علم النفس التجريبي في منتصف القرن الماضي وسيطرت علمائه على الأبحاث والدراسات التي ظهرت في تلك الفترة والتي كانت في مجملها تحاول إيجاد وفهم العمليات الإدراكية الحاصلة أثناء التعلم والأداء. إحدى الدراسات التي ظهرت في تلك الفترة و التي تعتبر نموذجا مميزا للعلاقة بين الإدراك والأداء الحركي, هي دراسة تداخل المحتويات التي حظيت منذ ظهورها بكثير من الأبحاث. أثبتت هذه الأبحاث وجود تأثير تداخل المحتويات, على عكس بعض النتائج الأخرى التي لم تثبت هذا التأثير. ارجع العلماء هذه النتائج لطبيعة المهام وخضوعها لتأثير برنامج حركي عام واحد . هذا البحث يشكل دراسة تطبيقية لتداخل المحتويات اعتماداً على مهارة التصويب في كرة السلة من نقاط مختلفة بهدف التحقق أو نفي أي تأثير لتداخل المحتويات في المهارات الحركية الأساسية التي تتكون منها الألعاب الرياضية و التي تخضع لتأثير برنامج حركي عام واحد .أظهرت نتائج البحث أن تداخل المحتويات يظهر في المهارات الحركية الأساسية التي تتكون منها الألعاب الرياضية التي تخضع لتأثير برنامج حركي عام واحد مما يشكل دعم تجريبي لاستخدام تداخل المحتويات خلال تعليم المهارات الحركية.With the advent of Experimental Psychology in the middle of the last century and took control of scientists on the research and studies that have appeared in that period, which was on the whole attempt to find and understand the cognitive processes taking place during the learning and performance of the studies that appeared in that period, and is a model unique to the relationship between cognition and motor performance Contextual Interference that have received since the appearance of the many studies that have proven the effect of overlapping content is that some of the results did not demonstrate this effect, scientists these results are attributed to the nature of the tasks and subject to the influence of one general motor program.This research is an applied study of overlapping content adopted in his experience on the skill of the correction in basketball from different points in order to verify or deny the impact of the emergence of overlapping content in skills which are subject to the influence of one general motor program.Find showed the impact of the emergence of overlapping content in skills which are subject to the influence of one general motor program, the results of which is a pilot for the use of unconditional support for overlapping content by teaching motor skills